Advancing Children's rights in detention : a model for international reform / Ursula Kilkelly and Pat Bergin ; with a foreword by Ann Skelton. - Kilkelly, Ursula; Bergin, Pat (Bristol University Press, 2022)
Drawing on Ireland's experience of transforming law, policy and practice, and combining theory with real-life experiences, this compelling book demonstrates how a progressive rights-based approach to child detention can be implemented.